1993
DOI: 10.1007/bf02191522
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical substrates of depression in the elderly

Abstract: The etiology of depression in the elderly is poorly understood. In this study, magnetic resonance imaging was used to evaluate the role of subcortical structures in the pathophysiology of depression in the elderly. Elderly depressed patients were found to have smaller caudate nuclei, smaller putaminal complexes and in increased frequency of subcortical hyperintensities compared with normal, healthy controls. These findings were more pronounced in patients with late-onset depression. Based on these findings, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
4
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(93 citation statements)
references
References 14 publications
5
81
4
2
Order By: Relevance
“…We should note here that our results do not replicate previously reported differences in caudate volumes between [12][13][14][15] and it is possible that the observed group differences were qualified by an interaction with age. Other studies examined a different age group than we did, 13 and many had smaller samples (e.g., patient groups of fewer than 30 individuals).…”
Section: J Psychiatry Neurosci 2017;42(3)contrasting
confidence: 99%
See 2 more Smart Citations
“…We should note here that our results do not replicate previously reported differences in caudate volumes between [12][13][14][15] and it is possible that the observed group differences were qualified by an interaction with age. Other studies examined a different age group than we did, 13 and many had smaller samples (e.g., patient groups of fewer than 30 individuals).…”
Section: J Psychiatry Neurosci 2017;42(3)contrasting
confidence: 99%
“…9,10 Finally, researchers have reported that the putamen is activated most strongly during anticipation of reward, whereas the caudate is activated most strongly during the receipt of reward. 8,10,11 A growing body of research indicates that adults with MDD have smaller volumes of the caudate [12][13][14][15] and putamen 13,14,16,17 than healthy controls. Postmortem studies have also reported smaller putamen volumes in depressed than in nondepressed adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are consistent with findings of frontal lobe impairment in biochemical (10), anatomical (11) and histological (9) investigations in the brains of patient with a history of depressive disorders (3,12).…”
Section: Jrc Almeida Et Alsupporting
confidence: 91%
“…28 One way vascular disease might lead an individual to develop LLD is by causing brain lesions that directly disrupt the neural network underlying mood and thus the capacity to regulate mood, and subsequently depressive symptoms. Though data supporting a causal link between vascular disease and LLD is difficult to obtain and thus lacking, correlative data supporting the vascular depression hypothesis include MRI studies of the brain of individuals with LLD showing increased rates of white-matter hyperintensities compared to non-depressed age-matched controls 32-33 and the finding that these white-matter hyperintensities correlate with functional changes in the mood neural network. 34 …”
Section: Current Hypotheses For Biological Mechanisms Promoting Lldmentioning
confidence: 99%